Queer: Heterosexual and homosexual in Tatakhulu Afrika’s Bitter Eden - Ordu, Stanley; Odukwu, Better (Goodwood Publishing, 2023)
Purpose: This study aimed to assess the depiction of homosexuality in Bitter Eden by Tatamkhulu Afrika, as well as the reasons for its positive or negative portrayal and the attitudes of gays and heterosexuals toward one another. Homosexuality covers homosexuality, lesbianism, bisexuality, transgender, and other so-called “sexual disorders.” Additionally, it is classified as a psychopathological disorder. Methodology/approach: The work adopted psychological and queer theory. And descriptive and qualitative methods of data analysis were used by grouping and having textual analysis. Results: In gender studies, feminism (s) and masculinity (ies) are major issues, whereas queer studies, which were long marginalized, are now garnering more attention in the West. However, queerness, particularly homosexuality, has received little creative and critical attention in Africa. As a result, this research would fill a need left by the paucity of literature on the issue. The result of the investigation demonstrates that when it comes to African environments, homosexuality is still weird. Limitations: The study is limited to one novel, Afrika (2002). Bitter Eden. Contributions: The study revealed that homosexuals are stigmatized in the chosen text. The study concluded that despite the presence of homosexuality in Africa, it is still largely a closet phenomenon.